The Third Global Forum : Framing the Health Workforce Agenda for Universal Health Coverage - Cometto, Giorgio; Boerma, Ties; Campbell, James; Dare, Lola; Evans, Tim (Elsevier, 2015)
Despite encouraging progress towards the health targets of the Millennium Development Goals (MDGs)—including improved child mortality and coverage of antiretroviral treatment and malaria interventions—many health systems in low-income and middle-income countries face structural challenges. Health workforce inadequacies are regarded as a major impediment, especially for maternal mortality targets.